Project finance in theory and practice : designing, structuring, and financing private and public projects - Gatti, Stefano, 1967- (Elsevier/Academic Press, 2008)
Project finance is a fast-growing area of capital investment for major infrastructure and other large projects. Financing such projects as EuroDisney, airports, highways, tunnels, schools, hospitals, and other large projects presents a complex and interesting challenge that the specialty of project finance takes on wholeheartedly, combining financial engineering with legal and contractual expertise to develop various financing options. In this book, Stefano Gatti of Bocconi University describes the theory that underpins this cutting-edge industry, and then provides illustrations and examples f.
Keywords: Public works -- Finance.; Construction industry -- Capital investments.; elektronické knihy; electronic books